Mapping global prevalence of menopausal symptoms among middle-aged women: a systematic review and meta-analysis - Yiqiao Fang; Fen Liu; Xinyue Zhang; Lei Chen; Yang Liu; Lin Yang; Xiaofeng Zheng; Jiaye Liu; Kewei Li; Zhihui Li (BMC, 2024)
Abstract Background Women at middle age are puzzled by a series of menopausal disturbances, can be distressing and considerably affect the personal, social and work lives. We aim to estimate the global prevalence of nineteen menopausal symptoms among middle-aged women by performing a systematic review and meta-analysis. Methods Comprehensive search was performed in multiple databases from January, 2000 to March, 2023 for relevant studies. Random-effect model with double-arcsine transformation was used for data analysis. Results A total of 321 studies comprised of 482,067 middle-aged women were included for further analysis. We found varied prevalence of menopausal symptoms, with the highest prevalence of joint and muscular discomfort (65.43%, 95% CI 62.51-68.29) and lowest of formication (20.5%, 95% CI 13.44-28.60). Notably, South America shared dramatically high prevalence in a sort of menopausal symptoms including depression and urogenital symptoms. Besides, countries with high incomes (49.72%) had a significantly lower prevalence of hot flashes than those with low (65.93%), lower-middle (54.17%), and upper-middle (54.72%, p < 0.01), while personal factors, such as menopausal stage, had an influence on most menopausal symptoms, particularly in vaginal dryness. Prevalence of vagina dryness in postmenopausal women (44.81%) was 2-fold higher than in premenopausal women (21.16%, p < 0.01). Furthermore, a remarkable distinction was observed between body mass index (BMI) and prevalence of sleep problems, depression, anxiety and urinary problems. Conclusion The prevalence of menopausal symptoms affected by both social and personal factors which calls for attention from general public.